2021
DOI: 10.1038/s41598-021-94996-7
|View full text |Cite
|
Sign up to set email alerts
|

Avian vampire fly (Philornis downsi) mortality differs across Darwin’s finch host species

Abstract: In invasive parasites, generalism is considered advantageous during the initial phase of introduction. Thereafter, fitness costs to parasites, such as host-specific mortality, can drive parasites towards specialism to avoid costly hosts. It is important to determine changes in host specificity of invasive populations to understand host-parasite dynamics and their effects on vulnerable host populations. We examined changes in mortality in the introduced avian vampire fly (Philornis downsi) (Diptera: Muscidae), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 89 publications
1
6
0
Order By: Relevance
“…N e was highest in 2006 and 2014 (but values for 2008 could not be obtained for the 10% missingness dataset), and lowest in 2020. Notably, this temporal decrease matches a decrease in mean in-nest P. downsi intensities (Common et al 2021) and daily catch rates of adult P. downsi across the sampling years (2014: 0.35 ± 0.03; Kleindorfer et al unpublished data;2020: 0.28 ± 0.02;Common et al 2022). The estimated values for effective population size were significantly smaller than expected, given the widespread distribution and high in-nest intensity of P. downsi.…”
Section: Effective Population Sizesupporting
confidence: 56%
See 1 more Smart Citation
“…N e was highest in 2006 and 2014 (but values for 2008 could not be obtained for the 10% missingness dataset), and lowest in 2020. Notably, this temporal decrease matches a decrease in mean in-nest P. downsi intensities (Common et al 2021) and daily catch rates of adult P. downsi across the sampling years (2014: 0.35 ± 0.03; Kleindorfer et al unpublished data;2020: 0.28 ± 0.02;Common et al 2022). The estimated values for effective population size were significantly smaller than expected, given the widespread distribution and high in-nest intensity of P. downsi.…”
Section: Effective Population Sizesupporting
confidence: 56%
“…1), but the number of reported males per female (i.e., rate of multiple mating) decreased ~ 35%. Concordantly, the genetically assigned females in 2020 had fewer offspring assigned to each of them per nest, with a smaller percentage of the infrapopulation assigned to each maternal genotype comparing time periods (2004-2006: 43 (2004( : 30.8 ± 16.5, Dudaniec et al 20102021: 43.4 ± 8.3;Common et al 2021). Our study did not detect any genetic clustering of P. downsi on Floreana Island across our four sampling years between 2006 and 2020, however F ST indicated some genetic differentiation between years.…”
Section: Discussionmentioning
confidence: 96%
“…We hypothesize that diapause is not observed because of a legacy of gene flow between areas with seasonal and continuous host breeding patterns in mainland South America, the native range of P. downsi . Philornis downsi is a generalist parasite of birds and is thus presumably able to parasitize hosts throughout the year in areas that experience year-round rainfall 65 , although a recent study in Galapagos found selection pressures acting on larval survival that may result in P. downsi shifting towards host specialization 66 . Within its native geographic range, P. downsi has been reared from the nests of multiple bird species throughout the year on Trinidad 15 and Brazil 67 , both characterized by humid conditions that support bird nesting throughout the year.…”
Section: Discussionmentioning
confidence: 99%
“…Another potential driver of this hybridisation are impacts from the introduced myiasiscausing 'avain vampire fly' Philornis downsi (Common, et al 2019;Fessl et al 2006), which causes anaemia, mortality and deformations of the nestling naris via larval blood and tissue parasitism (Common et al 2023, Katsis et al 2021, Kleindorfer and Dudaniec 2016. The number of P. downsi larvae in the nest predicts the size of naris deformation (Katsis et al 2021) and adult finches with enlarged nares from early-life parasitism produce low quality song that no longer differs between small and medium tree finches (Kleindorfer et al 2019).…”
Section: Introductionmentioning
confidence: 99%